Structural study of decrespignyite-(Y), a complex yttrium rare earth copper carbonate chloride, by three-dimensional electron and synchrotron powder diffraction - Rius, Jordi (2020)
The crystal structure of the mineral decrespignyite-(Y) from the Paratoo copper mine (South Australia) has been obtained by applying d recycling direct methods to 3D electron diffraction (ED) data followed by Rietveld refinements of synchrotron data. The unit cell is a = 8.5462(2), c = 22.731(2) Å and V = 1437.8(2) Å3, and the chemical formula for Z = 1 is (Y10.35REE1.43Ca0.52Cu5.31 σ17.61(CO3)14Cl2.21(OH)16.79• 18.35H2O (REE. rare earth elements). The ED data are compatible with the trigonal P 3m1 space group (no. 164) used for the structure solution (due to the disorder affecting part of the structure, the possibility of a monoclinic unit cell cannot completely be ruled out). The structure shows metal layers perpendicular to [001], with six independent positions for Y, REE and Cu (sites M1 to M4 are full, and sites M5 and M6 are partially vacant), and two other sites, Cu1 and Cu2, partially occupied by Cu. One characteristic of decrespignyite is the existence of hexanuclear (octahedral) oxo-hydroxo yttrium clusters [Y6(μ6-O)(μ3-OH)8O24] (site M1) with the 24 bridging O atoms belonging to two sets of symmetry-independent.CO3/2- ions, with the first set (2×) along a ternary axis giving rise to a layer of hexanuclear clusters and the second set (6×) tilted and connecting the hexanuclear clusters with hetero-tetranuclear ones hosting Cu, Y and REE (M2 and M3 sites). The rest of the crystal structure consists of two consecutive M3 C M4 layers containing the partially occupied M5, M6, and Cu2 sites and additional carbonate anions in between. The resulting structure model is compatible with the chemical analysis of the type material which is poorer in Cu and richer in (REE, Y) than the above-described material.